Meta-analyses of differences in blended and traditional learning outcomes and students' attitudes - Yu Z. (2023)
The sudden outbreak of COVID-19 has made blended learning widely accepted, followed by many studies committed to blended learning outcomes and student attitudes. Few studies have, however, focused on the summarized effect of blended learning. To complement this missing link, this study meta-analytically reviews blended learning outcomes and student attitudes by including 30 peer-reviewed journal articles and 70 effect sizes. It concludes that blended learning outcomes are significantly higher than the traditional learning outcomes with a medium effect size, and learners hold significantly more positive attitudes toward blended learning than traditional learning with a medium effect size. Blended learning may be promising, and information technology scientists may focus on the development of more advanced and effective devices to improve blended learning effectiveness.